Microenvironmental pH Modification in Buccal/Sublingual Dosage Forms for Systemic Drug Delivery - Shaolong He; Huiling Mu (MDPI AG, 2023)
Many drug candidates are poorly water-soluble. Microenvironmental pH (pHM) modification in buccal/sublingual dosage forms has attracted increasing interest as a promising pharmaceutical strategy to enhance the oral mucosal absorption of drugs with pH-dependent solubility. Optimizing drug absorption at the oral mucosa using pHM modification is considered to be a compromise between drug solubility and drug lipophilicity (Log D)/permeation. To create a desired pHM around formulations during the dissolution process, a suitable amount of pH modifiers should be added in the formulations, and the appropriate methods of pHM measurement are required. Despite pHM modification having been demonstrated to be effective in enhancing the oral mucosal absorption of drugs, some potential risks, such as oral mucosal irritation and teeth erosion caused by the pH modifiers, should not been neglected during the formulation design process. This review aims to provide a short introduction to the pHM modification concept in buccal/sublingual dosage forms, the properties of saliva related to pHM modification, as well as suitable drug candidates and pH modifiers for pHM modifying buccal/sublingual formulations. Additionally, the methods of pHM measurement, pHM modification methods and the corresponding challenges are summarized in the present review.